Antimicrobial extract of ficus deltoidea to control plant fungal pathogens - Zainal Kasim, Zainina (2016)
Around 85 percent of plant diseases are caused by fungal pathogens. Long term use of synthetic fungicides will lead to too much carcinogenic residue in soil and eventually will cause harm in terrestrial and aquatic biotic lives. It is beneficial to find alternative ways to control the widespread of fungal diseases using environmental-friendly approaches. The objectives of this study are to 1) extract antimicrobial compounds from the leaves of Ficus deltoidea and 2) determine the effect of the extracted antimicrobial compounds on the mycelial growth and spore germination of selected fungal pathogens in vitro. Two types of fungi were used, Rhizoctonia solani, and Ganoderma boninense. Leaves were washed and then ground. Five gram of leaf powder was diluted in distilled water and filtered using filter paper. The filtrate was used to test the inhibitory effect on mycelial growth of the selected fungal pathogens using poison agar technique in three replicates for each fungal pathogen at four different concentrations (5, 10, 15 and 20%) of leaf extracts and compared with control (0%). Poisoned agar plates containing F. deltoidea extract showed inhibition of mycelial growth, where percent inhibition of diameter growth (PIDG) of G. boninense was 55.9% at 7th day and R. solani 53.67% at 5th day. Meanwhile, there was 100% inhibition occurred for both G. boninense and R. solani at the concentrations of 10%, 15% and 20%. Thus, this showed that extracts of Ficus deltoidea has the potential to be used as a bio fungicide, a safe substitute to chemical fungicides.